2021
DOI: 10.3389/fmolb.2021.650264
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ferroptosis-Related Gene Signature Predicts Recurrence in Patients With Pancreatic Ductal Adenocarcinoma

Abstract: Background: Recurrence after surgery is largely responsible for the extremely poor outcomes for patients with pancreatic ductal adenocarcinoma (PDAC). Ferroptosis is implicated in chemotherapy sensitivity and tumor recurrence, we aimed to find out survival-associated ferroptosis-related genes and use them to build a practical risk model with the purpose to predict PDAC recurrence.Methods: Univariate Cox regression analysis was conducted to obtain prognostic ferroptosis-related genes in The Cancer Genome Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In each cohort, patients were divided into the high- or low-risk group according to the median value of the risk score. To compare the survival difference between high- and low-risk groups, Kaplan–Meier survival and receiver operating characteristic (ROC) analyses were conducted by using the R package “survival” and “timeROC.” We also calculated the time-varying concordance index (C-index) of our signature and compared it with six previous published signatures which were based on glycolysis ( Song et al, 2021 ), ferroptosis ( Feng et al, 2021a ), hypoxia ( Ding et al, 2021 ), m6A ( Meng et al, 2020 ), autophagy ( Yu J. et al, 2021 ), and immune ( Mao et al, 2021 ) related genes. The information of these six signatures are listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…In each cohort, patients were divided into the high- or low-risk group according to the median value of the risk score. To compare the survival difference between high- and low-risk groups, Kaplan–Meier survival and receiver operating characteristic (ROC) analyses were conducted by using the R package “survival” and “timeROC.” We also calculated the time-varying concordance index (C-index) of our signature and compared it with six previous published signatures which were based on glycolysis ( Song et al, 2021 ), ferroptosis ( Feng et al, 2021a ), hypoxia ( Ding et al, 2021 ), m6A ( Meng et al, 2020 ), autophagy ( Yu J. et al, 2021 ), and immune ( Mao et al, 2021 ) related genes. The information of these six signatures are listed in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Various ferroptosis-related genes (FRGs) are identified through the Cancer Genome Atlas (TCGA) and different genome analyses, which are utilized in developing risk models for pancreatic cancer (Table 2). Feng et al developed a risk model based on five FRGs, where CAV1, DDIT4, SRXN1, and TFAP2C indicate better survival, whereas SLC40A1 indicates a more adverse outcome [56]. Using ZNF419, TUBE1, STEAP3, SLC1A4, RRM2, PTGS2, MT1G, MAP3K5, DDIT4, CAPG, CAV1, BAP1, AURKA, and ATG4D, Jiang et al designed a prognostic FRGs risk model, in which it was shown that expression levels of PTGS2, RRM2, AURKA, CAV1, MAP3K5, and STEAPS are higher in tumor samples, and the upregulation of PTGS2 and the downregulation of MT1G, TUBE1, and ATG4D might contribute to tumorigenesis and poor outcomes [57].…”
Section: Immunogenetics 221 Ferroptosis-related Genes (Frgs) As Risk ...mentioning
confidence: 99%